2017
DOI: 10.1038/srep40937
|View full text |Cite
|
Sign up to set email alerts
|

Visual area V5/hMT+ contributes to perception of tactile motion direction: a TMS study

Abstract: Human imaging studies have reported activations associated with tactile motion perception in visual motion area V5/hMT+, primary somatosensory cortex (SI) and posterior parietal cortex (PPC; Brodmann areas 7/40). However, such studies cannot establish whether these areas are causally involved in tactile motion perception. We delivered double-pulse transcranial magnetic stimulation (TMS) while moving a single tactile point across the fingertip, and used signal detection theory to quantify perceptual sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Successful identification of a moving tactile stimulus of a symbolic nature relies on pre-existing cortical representations of these symbols and on working memory [3]. More recent studies have even demonstrated that kinetic tactile stimuli undergo processing in extrastriate dorsal visual regions [4]. Lesions anywhere along the afferent sensory pathways or those that affect the parietal lobe can lead to impairments in this recognition process [1,2,5], this condition is referred to as agraphesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Successful identification of a moving tactile stimulus of a symbolic nature relies on pre-existing cortical representations of these symbols and on working memory [3]. More recent studies have even demonstrated that kinetic tactile stimuli undergo processing in extrastriate dorsal visual regions [4]. Lesions anywhere along the afferent sensory pathways or those that affect the parietal lobe can lead to impairments in this recognition process [1,2,5], this condition is referred to as agraphesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely explanation for the change in the probability of leg selection induced by TMS over P3 is that the change in the cortical activity under P3 biased the selection process of the initial swing leg of gait initiation. P3 is considered to be the site over the left PPC [10][11][12]. Thus, our hypothesis, that the left PPC contributes to the selection process of the initial swing leg of gait initiation, is the most likely explanation for the effect.…”
Section: Contribution Of the Left Ppcmentioning
confidence: 87%
“…A coil was placed over F3, P3, F4 or P4. P3 is considered to be the site over the left PPC, and P4 is considered to be the site over the right PPC [10][11][12]. The participants wore a swim cap.…”
Section: Tms Sessionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, BA1 seems to subserve a similar function to 459 the middle temporal (MT)/V5 complex in visual motion processing [Pack 460 and Bensmaia, 2015]. Evidence from human studies suggests that tactile 461 motion also elicits more widespread activity in anterior intraparietal and 462 inferior parietal areas [Kitada et al, 2003], as well as activation of an area 463 of MT distinct from that implicated in visual motion [Summers et al, 2009, 464 Wacker et al, 2011, Amemiya et al, 2017]; however the latter may be an 465 epiphenomenon of visual imagery [Lacey and Sathian, 2011]. Directional 466 19/30 biases in tactile motion perception appear to be independent of visual 467 input, as tactile perceptual anisotropy has been observed previously in 468 blind individuals [Lechelt, 1988].…”
mentioning
confidence: 99%